Antimicrobial Resistance of Listeria monocytogenes Strains Isolated from Humans, Animals, and Food Products in Russia in 1950–1980, 2000–2005, and 2018–2021 - Pavel A. Andriyanov; Pavel A. Zhurilov; Elena A. Liskova; Tatyana I. Karpova; Elena V. Sokolova; Yulia K. Yushina; Elena V. Zaiko; Dagmara S. Bataeva; Olga L. Voronina; Ekaterina K. Psareva; Igor S. Tartakovsky; Denis V. Kolbasov; et al. (Antibiotics, 2021)
Susceptibility of 117 L. monocytogenes strains isolated during three time periods (1950–1980; 2000–2005, and 2018–2021) to 23 antibiotics was tested by the disk diffusion method. All strains were sensitive to aminoglycosides (gentamicin, kanamycin, neomycin, streptomycin), glycopeptides (vancomycin and teicoplanin), clarithromycin, levofloxacin, amoxicillin/clavulanic acid, and trimethoprim/sulfamethoxazole. Resistance to clindamycin was observed in 35.5% of strains. Resistance to carbapenems, imipenem and meropenem was found in 4% and 5% of strains, respectively. Resistance to erythromycin, penicillin G, trimethoprim, and ciprofloxacin was found in 4%, 3%, 3%, and 2.5% of strains, respectively. Resistance to tylosin, ampicillin, enrofloxacin, linezolid, chloramphenicol, and tetracycline was found in less than 2%. Three strains with multiple antibiotic resistance and 12 strains with resistance to two antibiotics were revealed. Comparison of strains isolated in different time periods showed that the percentage of resistant strains was the lowest among strains isolated before 1980, and no strains with multiple antibiotic resistance were found among them. Statistical analysis demonstrated that the temporal evolution of resistance in L. monocytogenes has an antibiotic-specific character. While resistance to some antibiotics such as ampicillin and penicillin G has gradually decreased in the population, resistance to other antibiotics acquired by particular strains in recent years has not been accompanied by changes in resistance of other strains.